Effect of Alcoholic Extract of Sour Orange Peel on Total Antioxidant, Insulin Level and Hyperglycemia in Alloxanized Rats - M Lakzaei (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Sour orange is known as an herbal plant in traditional medicine. Previous studies indicate a protective effect of citrus fruits or juices against risk of some chronic diseases such as diabetes. The aim of this study was to investigate the antioxidant and anti- hyperglycemic effects of alcoholic extract of sour orange peel in rats with alloxan induced hyperglycemia.METHODS: In this experimental study, there were 120 Wistar rats weighing 150-200 gr that were divided into 6 groups (20 rats in each group) divided into two time groups (24 and 48 h). Ethanol extract of sour orange peel was prepared. Animals were pretreated for 4 days in 2 different doses 100 and 300 mg/kg. 100 mg/kg bw alloxan injected intraperitoneally. After 24, 48 h blood sample collected and glucose (via glucose kit), serum antioxidant levels (via FRAP) and serum insulin levels (via ELISA assay) were measured and the groups were compared.FINDINGS: Twenty four hours after alloxan injection rats who received 300 mg/kg/day showed a significant increase in total antioxidant content (p=0.000) and significant increase in glucose level after 48 hours (p=0.001). The administration of sour orange peel extract (100 and 300 mg/kg/day) decreased serum insulin level in alloxan-induced hyperglycemic rats at 24 and 48 hours after alloxan injection (p<0.03).CONCLUSION: This study demonstrated that treatment with sour orange peel extract not only brought a significant increase insulin concentration but also decreased the insulin level and also increased glucose concentration in alloxanized rats.